Reinforcement Mechanism and Optimisation of Reinforcement Approach of a High and Steep Slope Using Prestressed Anchor Cables - Jian Li (Applied Sciences, 2019)
Using prestressed anchor cables is one of the most common approaches for reinforcing slopes. By establishing a calculation model for a high and steep slope, the changes of displacement of slope foot and increment of force on the cables under different prestresses were calculated. Furthermore, the influence of prestress on the changes of displacement of slope foot and force on the cables was analysed. By analysing the changes in force on cables in different parts of the slope, the reinforcement mechanism of a prestressed anchor cable on the slope was attained. The result showed that the reinforcement effect of prestressed anchor cable on the slope was mainly attributed to it effectively restricting the displacement of sliding mass in the slope, while the effect of cables in the lower part of the slope was more significant than that of those in the upper part of the slope. Therefore, to reduce the number of cables, decrease the construction difficulty of cables and save money, it is feasible to remove cables in the range of the upper-third of the slope. Afterwards, by improving the cable prestress in the range of the lower-third and reducing the cable prestress in the middle, the safety factor of the slope can satisfy design requirements, thus reinforcing the slope.